Performance Analysis of a Perturbed Circular DRA for Different Dielectric Materials - Behera, Pragyan Paramita; Kumar, M.Arun; Dash, Prabhu Prasad; Panda, Ribhu Abhusan; Choudhury, Barsha (Applied mechanics and materials, 2023)
The regular shape of a circular dielectric resonating antenna (DRA) is changed in this paper. The proposed dielectric resonator has a perturbed circular shape in which the least arc to arc distance is same as that of the wavelength (λ) that is calculated from the design frequency. The proposed structure has a substrate and a dielectric resonator which include dielectric materials. In this paper different dielectric materials have been used both for substrate as well as dielectric resonator and the performance of the proposed DRA has been evaluated in terms of S-Parameter ( <-10 dB) , antenna gain , radiation efficiency , directivity . The dielectric materials like FR4 epoxy and GaAs have been used for the substrate. For perturbed shaped dielectric resonator, the materials having high dielectric constant like silicon, alumina 92_pct.